Association of genetic variants at MYP10 and MYP15 with high myopia in a Han Chinese population. (4th May 2019) - Jiang, Lingxi; Zheng, Rui; Luo, Dongyan; Wang, Tingting; Zhai, Yaru; Ye, Zimeng; Liu, Xiaoqi; Gong, Bo; Qu, Chao; Shi, Yi
ABSTRACT: Background : Previous genome-wide association study (GWAS) has revealed the association between MYP10 at 8p23 and MYP15 at 10q21.1 and high myopia (HM) in a French population. This study is managed to discover the connection between some single nucleotide polymorphism (located at MYP10 and MYP15) and Han Chinese HM. Methods and Results : This case-control association study contained 1673 samples, including 869 ophthalmic patients and 804 controls. Twelve tag SNPs have been selected from the MYP10 and MYP15 loci and genotyped by SNaPshot method. Among 12 SNPs, rs4840437 and rs6989782 in TNKS gene were found significant association with HM. Carriers of rs4840437G allele and rs4840437GG genotype created a low risk of high myopia (P = .036, OR = 0.81, 95%CI = 0.71–0.93; P = .016, OR = 0.73, 95%CI = 0.56–0.96; respectively). Carriers of rs6989782T allele and rs6989782TT+CT genotype also had a decreased risk of high myopia (P = .048, OR = 0.82, 95%CI = 0.71–0.94; P = .006, OR = 0.74, 95%CI = 0.59–0.92; respectively). Other 10 SNPs displaced nonsignificant association with HM. Additionally, the risk haplotype AC and the protective haplotype GT, generated by two SNPs in TNKS, were considerably more likely to be association with HM (for AC, P = .002 and OR = 1.26; for GT, P = .027 and OR = 0.84). Conclusions : Our results demonstrated that some heritable variants in the TNKS gene are associated with HM in the Han population. The possible functions of TNKS in the development and pathogenesis of hereditary high myopia still require further researches to identify.